Investigating the association between COVID-19 vaccination and care home outbreak frequency and duration - Bradley, DT; Murphy, S; McWilliams, P; Arnold, S; Lavery, S; Murphy, J; de Lusignan, S; Hobbs, R; Tsang, RSM; Akbari, A; Torabi, F; Beggs, J; et al. (Elsevier, 2021)
Objectives At the end of 2020, many countries commenced a vaccination programme against SARS-CoV-2. Public health authorities aim to prevent and interrupt outbreaks of infectious disease in social care settings. We aimed to investigate the association between the introduction of the vaccination programme and the frequency and duration of COVID-19 outbreaks in Northern Ireland (NI).